Comparison of 12-lead and computer-analysed 3 orthogonal lead electocardiogram in coronary artery disease. Issue 8 (August 1976) - Murray, R G; Lorimer, A R; Dunn, F G; Macfarlane, P W; Hutton, I; Lawrie, T D
Abstract : The computer-analysed 3 orthogonal lead system ("3-lead ECG") provides a rapid and consistent interpretation of the electrocardiogram. In 102 patients undergoing selective coronary arteriography, the ability of such a system to predict the presence of absence of coronary artery disease and the site of myocardial ischaemia was compared with that of the conventional scalar electrocardiogram interpreted by cardiologists ("12-lead ECG"). Each system predicted the site of myocardial ischaemia with equal accuracy. The 3-lead ECG was a more sensitive index (3-lead ECG sensitivity=77%; 12-lead ECG sensitivity=70%) but less specific (3-lead ECG specificity=74%; 12-lead ECG specificity=78%). In coronary artery disease, the predictive "index of merit" for the 3-lead ECG was 0-51, compared with 0-48 for the 12-lead ECG. These results provide further justification for the routine use of the 3 orthogonal lead electrocardiogram.